Antibacterial Analysis of Andrographolide Against Selected Gram Positive and Negative Bacteria - Zaki, Muhammad; Multazam, Syamsul; Fakhrurrozi, Fakhrurrozi; Nawawi, Muhammad (Jurnal Biologi Tropis, 2025)
Andrographolide is an active compound extracted from Andrographis paniculata. It is commonly used in traditional medicine to reduce inflammation and fight bacteria. Studies show that andrographolide can stop bacteria from growing by disrupting their DNA and biofilm formation. It can also help regulate the immune system and lower inflammation caused by bacterial infections. Therefore, andrographolide has the potential to be an alternative to synthetic antibiotics, helping to prevent bacterial resistance and reduce side effects from synthetic antibiotic use. This study aims to investigate the potential antibacterial activity of andrographolide against S. aureus (ATCC 25923), S. epidermidis (ATCC 12228), K. pneumoniae (ATCC 70063), and P. aeruginosa (ATCC 9027). This study utilized the disc diffusion method to determine the inhibitory effects of andrographolide, as well as Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) assays to evaluate its bactericidal properties. Disc diffusion test (3.0 mg/mL) found that andrographolide can inhibit P. aeruginosa (23.70 mm), S. aureus (16.37 mm), S. epidermidis (19.77 mm), and K. pneumoniae (14.63 mm). The bacteria S. aureus, S. epidermidis, and K. pneumoniae have the same MIC and MBC values (1.5 mg/mL), while P. aeruginosa has a different value (0.75 mg/mL). These results indicate the bactericidal category at this concentration. Future research should explore how andrographolide works against various strains of bacteria and also investigate how andrographolide affects biofilms.